Naltrexone increases negatively-valenced facial responses to happy faces in female participants. (December 2016) - Meier, Isabell M.; Bos, Peter A.; Hamilton, Katie; Stein, Dan J.; van Honk, Jack; Malcolm-Smith, Susan
Highlights: Naltrexone increases negatively-valenced facial responses to affiliative cues. Blocking the mu-opioid system decreases motivation for social affiliation. Results support the mu-opioid system's role in adaptive socio-emotional behavior. Abstract: Positive social cues, like happy facial expressions, activate the brain's reward system and indicate interest in social affiliation. Facial mimicry of emotions, which is the predominantly automatic and unconscious imitation of another person's facial expression, has been shown to promote social affiliation. It has been demonstrated repeatedly that the opioid system is vital to social affiliation in rodents, but there is less evidence in humans. We investigated whether a 50 mg administration of naltrexone, an opioid antagonist with highest affinity for the mu-opioid system, modulates emotional mimicry. A passive viewing task with dynamic facial expressions was used in a randomized placebo controlled between-subjects design. Mimicry was measured with electromyography (EMG) on three facial muscles, the corrugator supercilii and the depressor jaw muscle, associated with negatively-valenced emotions, and the zygomaticus major, which is activated during smiling. The results demonstrate an increase of negatively-valenced facial responses (corrugator and depressor) to happy facial expressions after naltrexone compared to placebo, consistent with lowered interest in social interaction or affiliation. Our findings provide evidence for a role of the opioid system in modulating automatic behavioral responses to cues of reward and social interaction, and translate to rodent models of the mu-opioid system and social affiliation.